Heart of Education: The Relationship of Corporate Social Responsibility on the Organizational Commitment of Senior High School Teachers in Caloocan City, Philippines - Lumbang, Abram Andrew A.; Martin, Edwin (Future Science / FSH-PH Publications, 2022)
The research ventures into the connection between Senior High School (SHS) teachers’ organizational commitment (OC) in relation to their experiences on the dimension of Corporate Social Responsibility (CSR) done by their respective educational institutions. The study made use of the 5 CSR dimensions as basis of the experience of the SHS teachers, namely Human Rights and Labor, Environment, Economics, Product Responsibility, and Society. These were related side by side using the 3 Facets of OC which are Affective, Continuance, and Normative. Quantitative and qualitative data analyses have been used to confirm a relationship between the SHS teachers’ OC and the level of experience on the dimensions of CSR. General findings of the study show that problems of scheduling, effectivity and assessment hinders the level of OC that SHS teachers have towards the CSR activities of their educational institution. To address the issue, the research provided a set of suggestions to optimize the CSR in improving the OC of teachers through proper forms of pre-evaluation procedures, post assessment procedures and a set of effective mix of internal and external CSR program recommendations.